2019
DOI: 10.4283/jmag.2019.24.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat Transfer Enrichment in Hydromagnetic Flow of Hybrid Nanofluid Along Vertical Wavy Surface

Abstract: The hybrid nanofluids are novel nanofluids and can be made by adding different types of nanoparticles in the plain fluid. The mathematical modeling of hybrid nanofluid under the magnetic influence over a vertical wavy surface is developed in the present theoretical investigation. The analysis is performed for hybrid nanofluid consisting of Al 2 O 3-SiO 2 nanoparticles and compared with SiO 2 nanoparticle. The theoretical results also indicate that Al 2 O 3-SiO 2 water hybrid nanofluid have higher heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In light of the above‐stated facts, the BCs assigned to this flow problem are written as 43,51 truey¯=trueS¯(truex¯): trueu¯=0, truev¯=0, T=Tw1emfor all truex¯>0, truey¯: trueu¯=0,true p¯=p, T=T for all truex¯>0.…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the above‐stated facts, the BCs assigned to this flow problem are written as 43,51 truey¯=trueS¯(truex¯): trueu¯=0, truev¯=0, T=Tw1emfor all truex¯>0, truey¯: trueu¯=0,true p¯=p, T=T for all truex¯>0.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Groşan et al 42 discussed thermophoretic transport phenomena in a heated wavy cavity and noted that the number of oscillations improves the Nusselt number and fluid flow strength. Iqbal et al 43 considered the heat transfer analysis due to Al2O3SiO2/water HNF through a vertical wavy texture and showed that the ratio of these nanoparticles in the Al2O3SiO2 binary nanofluid heat transfer rate can be adjusted as needed. Some studies on related mathematics and physics are mentioned in References [44–59].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of internal heat generation in the flow of MoS 2 -SiO 2 /C 3 H 8 O 2 is studied by Shaiq et al [ 13 ] Khan et al [ 14 ] analyzed entropy generation analysis of MoS 2 -SiO 2 /C 3 H 8 O 2 nanofluid with variable viscosity. Heat transfer enhancement in hybrid nanofluid along the wavy surface is studied by Iqbal et al [ 15 ]. It is noted that hybrid nanofluid has a higher transfer rate than nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Important physics, primary understanding, and beneficial contributions to the analysis of convection phenomena in fluid flow along wavy texture are given in [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%